Association Between Public Health Expenditure and COVID-19 Management Outcomes in India: An Ecological Cross-Sectional Study - Alok Ranjan Dutta; Chumki Handique (National Journal of Community Medicine, 2026)
Background: Public health expenditure plays an important role in strengthening health-system capacity and preparedness during public health emergencies. This study examined the association between public health expenditure and COVID-19 management outcomes across Indian states. Methods: An ecological cross-sectional study was conducted using secondary data from 29 Indian states during the first wave of the COVID-19 pandemic. COVID-19 data were obtained from the MyGov India COVID-19 Dashboard, while public health expenditure and other variables were sourced from government databases. The primary exposure variable was the average share of public health expenditure in total state expenditure during 2009-2018. Pearson correlation analysis assessed associations with health infrastructure, and ordinary least squares regression examined associations with COVID-19 deaths per 100 confirmed cases and COVID-19 tests per million population, adjusting for per capita NSDP and, in separate models, population density and the proportion of the population aged 60 years and above. Results: Higher public health expenditure was associated with lower population served per public health institution and greater availability of government doctors and hospital beds. It was also significantly associated with lower COVID-19 deaths per 100 confirmed cases (β = -0.42; 95% CI: -0.83, -0.06; p = 0.04) and higher COVID-19 testing rates per million population (β = 6496; 95% CI: 511, 12481; p = 0.04). Conclusion: Sustained public investment in health may strengthen health-system preparedness and resilience during public health emergencies.